OPTIMALISASI KUALITAS AIR TERHADAP PERTUMBUHAN BENIH IKAN NILA (Oreochromis niloticus) - Ramadhana, Sri (Fakultas Pertanian UVAYA Banjarmasin, 2022)
This study aims to determine the relationship between water quality parameters and the daily growth rate of tilapia. Research method A case study with a qualitative approach to water quality. The observation period is 30 days. The average fish size of tilapia was 10 g/fish as many as 50 individuals on a single observation. Aquarium size 50 x 30 x 30 cm, with a volume of 37.5 liters of water. The feed used is PF 1000 pellets (PT Matahari Sakti) with a frequency of 5% of the fish weight and a frequency of feeding 2 times per day (morning and evening). The results of the study showed that Morning Temperature ranged from 26.3 – 26.5oC with a difference of 0.02oC. Afternoon temperatures range from 28.3-28.5oC with a difference of 0.02oC. The temperature range in the morning and evening is 26.3 – 28.5. Fluctuations are 2.2 oC. Dissolved oxygen ranges from 4.75 - 5.14 mg/L. The pH of the water is in the range of 6.67 – 6.95 Ammonia 0.057 - 0.36 mg/L. The results of the overall correlation analysis show that the water quality parameters do not have a significant effect on the daily growth rate of tilapia so the water quality parameters are in a good range for the life and growth of tilapia